PENGARUH PENGEMBANGAN KARIR TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. PLN (PERSERO) UP3 BIMA - Ari Afriansyah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This study aims to determine the morale of employees at PT. PLN (PERSERO) UP3 BIMA. Where the sample used is 43 permanent employees. The results of the validity test indicate that the career development and work spirit variables are all declared valid because r correlation > r comparison 0.300, the reliability results of the statement instrument on career development variables (X) and work spirit (Y) obtained Cronbach's Alpha Career Development (X) values of 0.906 and Work Morale (Y) of 0.936 and in accordance with existing standards, the Cronbach's Alpha value is > 0.60, which means that all the answer items on the questionnaire are declared reliable. morale value is 19,309. The career development variable regression coefficient is 0.662; This means that if career development has increased by one unit, then the morale will increase or increase by 0.662. The results of the correlation coefficient obtained a simple correlation coefficient value of 0.613, The results of the coefficient of determination obtained a coefficient of determination (R Square) of 0.375 or 37.5 The % level of influence is said to be low, while the remaining 62.5 is influenced by other variables not examined in this study. T-test results (partial) Based on the SPSS output in the t-test table above, the t-count value is 4.963 and the sig value of 0.000 will then be compared with the t-table value of 2.019, it can be concluded that the t-count value is greater than t-table (4.963 > 2.019 ) and the sig value obtained is 0.000 less than 0.05 (0.000 <0.05) so Ha is accepted and H0 is rejected, which means career development has a positive and significant effect on employee morale at PT PLN (PERSERO) UP3 Bima.